PRAGMATIC PROBLEMS OF TRANSLATION (Лучшие интеллектуальные исследования, 2025)
Abstract: Translation is not merely a linguistic transformation but also a pragmatic act that requires consideration of context, speaker intention, and cultural nuances. Pragmatic problems in translation often arise when translators fail to accurately convey implied meanings, speech acts, or culturally specific references from the source language into the target language. This article explores the nature of pragmatic issues in translation, including speech act theory, implicature, deixis, politeness strategies, and culture-bound expressions. Through examples and case studies, it highlights how misinterpretations or lack of equivalence in pragmatic elements can lead to distorted meaning or communication failure. The article also discusses possible strategies to overcome pragmatic challenges in translation, emphasizing the importance of contextual awareness and cultural competence.